A comparison of internal jugular vein cannulation versus supraclavicular brachiocephalic vein cannulation using ultrasound guidance - Zulfiqar Ali; Abdul Waheed Mir; Iqra Nazir; Sajad Hussain Arif; Altaf Mir; Mir Mohsin; Zoya Sehar; Shahid Ahmad Mir (Asian Journal of Medical Sciences, 2024)
Background: Ultrasound has become the standard of care for the insertion of central venous catheters (CVCs) in the intensive care unit. With the introduction of ultrasonography in CVC insertion, there has been an improvement in the success rate and a dramatic decrease in the rate of complications.